Improving of The Student Learning in Lectures of General Physics I by Collaborative Learning Model Based on Saintific Approach - Panggabean, D. D.; Irfandi, I.; Sinuraya, J. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2017)
This research aim is improving the learning outcomes of the students on General Physics course I. This research was done at Physics Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Medan. The Collaborative Learning Model is based on a Scientific Approach. There are three subject matters: Kinematics, Dynamics, Effort and Energy. A set of 20 multiple choice questions was used in each cycle as the instrument to measure the student's learning outcomes which had been predictively validated. Based on SPSS 17.0 analysis result, this instrument was declared valid and has had high reliability. For each cycle a pre-test and post-test were implemented. The result shows that there is a significant increase of student learning outcomes for each cycle in respect to the value of normalized gain.